The genus Cyriocosmus Simon 1903 and two new species from Peru (Araneae: Theraphosidae: Theraphosinae) - Kaderka, Radan (2019)
A female of Cyriocosmus giganteus Kaderka 2016 is described and illustrated for the first time, a new diagnosis of this species is proposed. Cyriocosmus paredesi sp. nov. from Quebrada Putuiman (Marañon River) and Cyriocosmus foliatus sp. nov. from Umaral near Iquitos, both from Loreto Department in Peru, are described, diagnosed, illustrated and keyed. The male of Cyriocosmus sellatus (Simon 1889) from Rio Blanco, the tributary of Rio Tahuyao, Loreto Department in Peru, is redescribed and figured. The distribution area of this species is updated, and difficulties in the identification of this species are discussed.